2014
DOI: 10.1007/s00277-014-2206-x
|View full text |Cite
|
Sign up to set email alerts
|

Deguelin, a selective silencer of the NPM1 mutant, potentiates apoptosis and induces differentiation in AML cells carrying the NPM1 mutation

Abstract: Nucleophosmin (NPM1) is a multifunctional protein that functions as a molecular chaperone, shuttling between the nucleolus and the cytoplasm. In up to one third of patients with acute myeloid leukemia, mutation of NPM1 results in the aberrant cytoplasmic accumulation of mutant protein and is thought to be responsible for leukemogenesis. Deguelin, a rotenoid isolated from several plant species, has been shown to be a strong anti-tumor agent. Human leukemia cell lines were used for in vitro studies. Drug efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…In the NPM1 wild-type AML cell lines, besides a slight effect of ATO/ATRA combination in U937, ATO/ATRA pretreatment did not show any effect on DNR sensitivity ( Figure 6C-D). Although observed mainly in OCI/AML3, these findings are in keeping with previous reports showing that downregulation of NPM1 sensitizes AML cells to chemotherapy [31][32][33][34][35] and has clinical implications.…”
Section: Npm1 Mutant Oncoprotein Degradation Upon Ato/atra Treatmentsupporting
confidence: 79%
See 1 more Smart Citation
“…In the NPM1 wild-type AML cell lines, besides a slight effect of ATO/ATRA combination in U937, ATO/ATRA pretreatment did not show any effect on DNR sensitivity ( Figure 6C-D). Although observed mainly in OCI/AML3, these findings are in keeping with previous reports showing that downregulation of NPM1 sensitizes AML cells to chemotherapy [31][32][33][34][35] and has clinical implications.…”
Section: Npm1 Mutant Oncoprotein Degradation Upon Ato/atra Treatmentsupporting
confidence: 79%
“…Evidence that NPM1 mutant downregulation can be a suitable way to target NPM1-mutated AML cells comes also from previous reports showing that NPM1 mutant silencing either by drugs (ie, deguelin, 33 and (-)-epigallocatechin-3-gallate 34 ) or inhibitory RNA 31 leads to apoptosis and sensitizes cells to chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…ECGT is the major polyphenol extracted from green tea, widely investigated for its antioxidant properties and for its possible effects in cancer prevention [123]. In both cases it was shown that treatment of OCI-AML3 cells with deguelin [124] and of IMS-M2 cells (also expressing NPM1c+) with ECGT [125], was effective in reducing NPM1c+ but not NPM1wt levels and in inducing apoptosis. NPM1 levels were instead not consistently affected when treating AML cell lines expressing NPM1wt only [124].…”
Section: Atra/arsenic Oxide Deguelin and (−)-Epigallocatechin-3-gallatementioning
confidence: 99%
“…Cell growth inhibition after GA treatment was examined with MTT assays, as previously described (Yi et al, 2015).…”
Section: Cell Growth Inhibition Assaymentioning
confidence: 99%